2014
DOI: 10.1126/scitranslmed.3007803
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cell-Free DNA Enables Noninvasive Diagnosis of Heart Transplant Rejection

Abstract: Monitoring allograft health is an important component of posttransplant therapy. Endomyocardial biopsy is the current gold standard for cardiac allograft monitoring but is an expensive and invasive procedure. Proof of principle of a universal, noninvasive diagnostic method based on high-throughput screening of circulating cell-free donor-derived DNA (cfdDNA) was recently demonstrated in a small retrospective cohort. We present the results of a prospective cohort study (65 patients, 565 samples) that tested the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
407
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 446 publications
(429 citation statements)
references
References 22 publications
16
407
0
6
Order By: Relevance
“…In heart transplant recipients, De Vlaminck and coworkers reported a mean plasma ddcfDNA fraction of 3.8% on the first day posttransplant, which declined within 1 week to a baseline level of 0.06% for the following year during stable graft conditions (45). Other studies reported plasma ddcfDNA fractions of approximately 0.9% in cardiac recipients with stable graft function (34,42) ( Table 3).…”
Section: Kinetics Of Ddcfdna Levels In Recipients With Stable Graftsmentioning
confidence: 86%
See 2 more Smart Citations
“…In heart transplant recipients, De Vlaminck and coworkers reported a mean plasma ddcfDNA fraction of 3.8% on the first day posttransplant, which declined within 1 week to a baseline level of 0.06% for the following year during stable graft conditions (45). Other studies reported plasma ddcfDNA fractions of approximately 0.9% in cardiac recipients with stable graft function (34,42) ( Table 3).…”
Section: Kinetics Of Ddcfdna Levels In Recipients With Stable Graftsmentioning
confidence: 86%
“…While amplification of Y-chromosome genes in the recipient's plasma and urine has been widely used in gender-mismatched transplantations (21,22,30,31,(34)(35)(36)(37)(38)(39), this strategy is limited to about 25% of the transplant population. A more universal approach is the use of informative genetic polymorphisms whereby a particular allele differs or is absent in the donor genome compared to the recipient genome; in addition to the quantification of donor-specific human leukocyte antigen deoxyribonucleic acid (HLA DNA) (40) and copy number deletion polymorphisms (41), single nucleotide polymorphisms (SNPs) can be targeted to determine the percentage of ddcfDNA by counting donor and recipient's bases at informative SNP sites with digital droplet polymerase chain reaction (ddPCR) (42)(43)(44) or massive parallel shotgun sequencing (MPSS) (34,45).…”
Section: Cell-free Dna Isolation and Quantification: Technical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not only human cells that shed their nucleic acids into the blood: DNA from plant-based foods has been detected (15), and other life forms such as viruses, bacteria, and fungi release their DNA and RNA into the blood, a phenomenon which has been exploited to determine the presence of infectious disease (12,16) and to measure alterations of the virome due to pharmacological immunosuppression (17). There are roughly an order of magnitude more nonhuman cells than nucleated human cells in the body (18,19); combining this observation with the average genome sizes of a human, bacterium, and virus (Gb, Mb, and kb, respectively) suggests that approximately 1% of DNA by mass in a human is derived from nonhost origins.…”
mentioning
confidence: 99%
“…The existence of circulating nucleic acids in blood has been known since the mid-20th century (10), but only in the last few years has the advent of high-throughput sequencing led to clinical diagnostics based on these nucleic acids [also known as cell-free DNA (cfDNA) or RNA], including detecting fetal abnormalities (11), transplanted organ rejection events (12,13), and signatures of cancers (14). It is not only human cells that shed their nucleic acids into the blood: DNA from plant-based foods has been detected (15), and other life forms such as viruses, bacteria, and fungi release their DNA and RNA into the blood, a phenomenon which has been exploited to determine the presence of infectious disease (12,16) and to measure alterations of the virome due to pharmacological immunosuppression (17).…”
mentioning
confidence: 99%